Weather Information for Tribune - H. D. Bond; J. Slattery (Kansas Agricultural Experiment Station Research Reports, 2020)
Summary of 2019 weather for research conducted at the Tribune field location.
Keywords: Tribune weather; 2019 weather; southwest Kansas weather report